Posting About Cancer: Predicting Social Support in Imgur Comments. (October 2020) - Hale, Brent J.; Collins, Ryan; Brown, Danielle K.
People who are affected by cancer can benefit greatly from social support and digital social networks, though our understanding of online support is primarily founded in dominant platforms like Facebook . In addition, while previous scholarship indicates that social support is available online, little research has examined predictors of support provision. A content analysis was performed to examine the relationship between narrative features in Imgur posts and social support in comments. Imgur (Imgur.com ) is a social media site and image-hosting platform, amassing over 250 million monthly visitors. Six post features were hypothesized to predict support, including explanations of the diagnosis experience, evidence of agentive problem solving, indications of positive reappraisal, pleads for the audience to get a checkup, references to mortality, and inclusion of humor. The results of this study indicate a relationship between narrative construction and social support, finding that the inclusion of narrative features in cancer-related posts influenced the provision of support in comments. Findings of this study could have implications for a multitude of stakeholders interested in social support provision, including healthcare professionals and researchers interested in the use of social media platforms for support, and organizations interested in designing supportive online platforms for individuals coping with cancer.